Meningkatkan Kualitas Guru untuk Menjawab Tantangan Abad 21 - Faliki, Afiq Naufal; Nurkhasanah, Alfiana Tri; Soraya, Endah; Chamdani, Muhamad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Teacher quality is a key factor in the success of education, especially in facing the challenges of 21st-century learning, which demands digital literacy, critical thinking, creativity, collaboration, and effective communication. This study aims to systematically review the literature related to improving teacher quality within this context. The method used is a Systematic Literature Review (SLR) of ten selected articles published between 2018 and 2023, sourced from Google Scholar based on scientific credibility and relevance. The review findings indicate that improving teacher quality involves mastery of educational technology, pedagogical competence, reflective thinking skills, and strong professional character. In addition, continuous training, learning communities, and adaptive educational policies also play a significant role in preparing teachers for changing times. Therefore, a comprehensive, sustainable, and needs-based strategy is essential to enhance teacher quality and support educators in adapting and innovating in the teaching and learning process.Kualitas guru merupakan kunci keberhasilan pendidikan, terutama dalam menghadapi tantangan abad ke-21 yang menuntut literasi digital, berpikir kritis, kreativitas, kolaborasi, dan komunikasi efektif. Penelitian ini bertujuan menelaah literatur secara sistematis terkait peningkatan kualitas guru dalam konteks tersebut. Metode yang digunakan adalah Systematic Literature Review (SLR) terhadap sepuluh artikel terpilih yang diterbitkan pada 2018–2023 melalui penelusuran Google Scholar berdasarkan kriteria keilmiahan dan relevansi. Hasil kajian menunjukkan bahwa peningkatan kualitas guru mencakup penguasaan teknologi pendidikan, kompetensi pedagogik, kemampuan reflektif, dan karakter profesional. Selain itu, pelatihan berkelanjutan, komunitas belajar, serta kebijakan pendidikan yang adaptif turut mendukung kesiapan guru menghadapi perubahan zaman. Oleh karena itu, diperlukan strategi peningkatan mutu guru yang menyeluruh, berkelanjutan, dan sesuai dengan kebutuhan nyata di lapangan guna menciptakan tenaga pendidik yang mampu beradaptasi dan berinovasi dalam proses pembelajaran.